Never too late to exercise - Kamaruzaman, Nor Azam (2020)
Regular exercise reduces 30-40% the risk for Cardiovascular death even when started in middle age. The risk reductions in subjects who only became active in midlife were SIMILAR to those who had maintained high Leisure Time Physical Activity from adolescence.